KEAMANAN MANUSIA DALAM PENANGANAN PERDAGANGAN MANUSIA: ANALISIS PERAN IOM MENANGANI HUMAN TRAFFICKING - Sofjan, Noorwahid (Program Studi Pemikiran Politik Islam, Fakultas Ushuluddin, Adab, dan Dakwah IAIN Palu, 2024)
Abstract The most crucial thing about human trafficking is that the activity does not disappear and even continues to show increasing numbers of victims. Handling cannot be carried out only by the government or by state officials but requires comprehensive handling from all levels of society. This research aims to highlight the role of an organization in dealing with these problems using a human security approach. Descriptively and qualitatively the facts are analyzed and produce several conclusions: a). efforts to help, defend, rescue based on existing laws which are more outward in nature, but also on efforts to implement human rights values ​​from within. Apart from being an ethical basis, human values ​​are also implemented in every action. b). The problem of human trafficking cannot be separated from structural dimensions such as the fulfillment of welfare, justice and development policies which influence all dimensions of human livelihood. c). The best prevention is through education, providing employment opportunities, welfare and the most important thing is to provide a sense of security for all citizens.